2019
DOI: 10.1002/jia2.25371
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the HIV undiagnosed population in Belgium reveals higher prevalence for MSM with foreign nationality and for geographic areas hosting big cities

Abstract: Introduction Increasing our knowledge on geographic areas and key populations most affected by HIV is essential to improve prevention and care and to ensure a more focused HIV response. Here, we estimated the prevalence of undiagnosed HIV infections in Belgium and its distribution across geographic areas and exposure groups. Methods We used surveillance data on newly diagnosed HIV cases and a previously developed back‐calculation model to estimate number and prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This may be surprising given that prenatal HIV screening offers constitute HIV testing opportunities for women in both countries. However, a recent study using mathematical modelling in Belgium showed that indeed women of sub-Saharan African origin have a high risk of being undiagnosed [59]. Migration status may be one of the structural factors impeding access [60,61], but future research should explore this finding in more detail.…”
Section: Discussionmentioning
confidence: 96%
“…This may be surprising given that prenatal HIV screening offers constitute HIV testing opportunities for women in both countries. However, a recent study using mathematical modelling in Belgium showed that indeed women of sub-Saharan African origin have a high risk of being undiagnosed [59]. Migration status may be one of the structural factors impeding access [60,61], but future research should explore this finding in more detail.…”
Section: Discussionmentioning
confidence: 96%
“…Overall point estimates of the proportion undiagnosed in 2018 using the ECDC modelling tool ranged from 7.1% (355 undiagnosed infections) using default model assumptions for CD4 distribution, to 10.2% (520 undiagnosed infections) with the Danish CD4 proxy, which is amongst the lowest in Europe, and comparable to estimates from neighbouring Denmark and Sweden [13,15,41,42]. National surveillance data and clinical data from the capital, Oslo, support that there is a low proportion undiagnosed in Norway, with a decreasing total number of first-time diagnoses, low proportion of late diagnoses and high proportion achieving viral suppression [17,27].…”
Section: Discussionmentioning
confidence: 97%
“…The HIV European Research on Mathematical Modeling and Experimentation of HIV Testing in Hidden Communities (HERMETIC) project applies a mathematical model for routine HIV-surveillance data to calculate the size and proportion of these undiagnosed HIV-infected populations. Modeling results obtained using a back-calculation method [ 5 ] for Belgium indicate that almost 2818 people living with HIV remained undiagnosed in 2015, corresponding to a prevalence rate of 4.1 undiagnosed persons per 10,000 [ 6 ]. The most affected populations were non-Belgian MSM (almost 264 undiagnosed persons per 10,000), SAMs with a higher proportion among women (about 173 per 10,000) than among men (about 93 per 10,000), and Belgian MSM (about 55 per 10,000) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling results obtained using a back-calculation method [ 5 ] for Belgium indicate that almost 2818 people living with HIV remained undiagnosed in 2015, corresponding to a prevalence rate of 4.1 undiagnosed persons per 10,000 [ 6 ]. The most affected populations were non-Belgian MSM (almost 264 undiagnosed persons per 10,000), SAMs with a higher proportion among women (about 173 per 10,000) than among men (about 93 per 10,000), and Belgian MSM (about 55 per 10,000) [ 6 ]. While Belgian HIV-testing rates are relatively high and cost-effective with 1.25 new HIV diagnoses per 1000 tests [ 4 , 7 ], these estimates of undiagnosed HIV infections indicate that current HIV-testing strategies fail to reach all people at risk of infection in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation